Inhibition of cyclin E1 sensitizes hepatocellular carcinoma cells to regorafenib by mcl-1 suppression - Xu, Jianliang (Cell Commun Signal, 2019)
BACKGROUND: To clarify the effects of cylcin E1 expression on HCC tumor progression, we studied the expression of cyclin E1 and inhibitory efficacy of regorafenib and sorafenib in HCC cells, and investigated a potential therapy that combines regorafenib treatment with cyclin E1 inhibition. METHODS: Western blotting for caspase-3 and Hoechst 33225 staining was used to measure the expression level of apoptosis-related proteins under drug treatment. RESULTS: Our results showed that enhanced expression of cyclin E1 after transfection compromised apoptosis in HCC cells induced by regorafenib or sorafenib. Conversely, down-regulation of cyclin E1 gene expression or inhibition of cyclin E1 by the cyclin-dependent kinase (CDK) inhibitors dinaciclib (DIN) or flavopiridol sensitized HCC cells to regorafenib and sorafenib by inducing apoptosis. The expression of Mcl-1, which is modulated by STAT3, plays a key role in regulating the therapeutic effects of CDK inhibitors. Xenograft experiments conducted to test the efficacy of regorafenib combined with DIN showed dramatic tumor inhibitory effects due to induction of apoptosis. Our results suggested that the level of cyclin E1 expression in HCCs may be used as a pharmacodynamic biomarker to assess the antitumor effects of regorafenib or sorafenib. CONCLUSIONS: Combining regorafenib and CDK inhibitors may enhance the clinical efficiency of the treatment of HCCs. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12964-019-0398-3) contains supplementary material, which is available to authorized users.